P1384Radiation safety and electrophysiologists: radiation protection status. (18th June 2020) - Krzowski, B; Gawalko, M; Peller, M; Balsam, P; Lodzinski, P; Grabowski, M; Opolski, G; Kosiuk, J
Abstract: INTRODUCTION:  Ionizing radiation is typically used during variety electrophysiological (EP) procedures, although it may contribute to deterministic effects especially for staff.  PURPOSE:  The purpose of this study was to perform an analysis of EP operators' radiation protective devices for occupational exposure.  METHODS:  Data reported herein were gathered from international, multi-site,  prospective, Go 4 Zero Fluoroscopy registry. The registry encompassed 25 European EP centers, and up to 5 operators from each center. The presence of operators' X-ray protection tools was examined to determine the level of operators' protection. Additionally, the tests included availability of measures to decrease radiation output and exposure control measures. Finally, the analysis of correlation between the X-ray protection and degree of operators' experience (<5, 5-15, >15 years) as well as number of procedures performed per month (1-9, 10-19, 20-39, >40 procedures/month) was performed.  RESULTS:  Our analysis included 95 operators (median age: 39 years, 85% of male, median training time: 5 years). The whole study group performed annually medical examinations due to radiation exposure and 56% of them received dosimetry reports once a month, 5% - once every 3 months, and 39% - once a year. Irrespectively of experience or number of performed procedures the most frequently used X-ray protection tools (used by >80% of group) were lead apron, thyroid shields, screen below the table, glass in the lab, and least often (used by < 6% of group) – protective gloves and cabin. The most often exposure control measures used were chest (95%) followed by collar (31%), ring (24%) and eye (7%) dosimeters. The inverse correlation between level of experience and measures to decrease radiation output was observed (collimation: 84%, 80% and 78%; minimizing the tube-to intensifier distance: 100%, 93% and 91% of operators with <5, 5-15 and >15 years of experience, respectively). There were not observed differences between type of radiation protection equipment and operators' level of experience or number of procedures. Additionally, there were no differences between male and female operators regarding protective equipment, expect eyeglasses or cabin that were more often used by men. Operators who were protected by >4 X-ray protection tools were exposed for higher radiation levels as compared to those protected by <4 X-ray protection tools (median [IQR] radiation exposure: 0.6 [0.2-1.1] vs 0.2 [0.1-0.2] mSv per month, p < 0.0001; 1.1 [0.1-12.0] vs 0.5 [0.1-1.1] mSv per year, p < 0.0001). There were no differences between the type of (universitary vs non-universitary) or institution's localization (Eastern vs Central vs Western Europe) and used protective equipment.   CONCLUSIONS:  Both proper radiation protective equipment, and regular medical examination due to professional exposure are mandatory to reduce radiation exposure in practice.